Analysis of Factors Affecting FEB UB Student’s Shopee Paylater Consumption Behavior - Khalisa, Fitra; Suryo Bintoro, Nugroho (Contemporary Studies in Economic, Finance and Banking, 2025)
The rapid adoption of digital financial technology, including Buy Now, Pay Later (BNPL) services, has changed consumer behaviour patterns. Shopee PayLater has emerged as a popular payment option, especially among college students. Despite being increasingly used, this service may increase the risk of uncontrolled consumptive behaviour. This study aims to analyze the factors that influence the consumption behaviour of students of the Faculty of Economics and Business, Universitas Brawijaya, using Shopee PayLater. This study uses a quantitative approach and a survey of 119 respondents. It analyzes how Shopee PayLater, income, expenses, and financial literacy influence student consumption behaviour. The regression analysis results show that the use of Shopee PayLater and spending have a significant effect on consumption behaviour. In contrast, income and financial literacy have no significant effect. The implications of this study emphasize the need to increase practice-based financial literacy and stricter regulations on digital credit services to reduce the risk of excessive consumption among college students.